Emmer Wheat and Barley Prices in the Late New Kingdom: A Ramessid Price Paradox Resolved. Issue 1 (June 2018) - van Pelt, W. Paul; Heinrich, Frits
This brief contribution uses archaeobotanical data to quantify the edible weight and energetic value of a khar of emmer wheat and a khar of barley. It then combines these data with emmer and barley prices from late New Kingdom Deir el-Medina to argue that, contrary to conventional wisdom, emmer wheat was more expensive per calorie than barley during most of this period. It furthermore argues that emmer wheat and barley were delivered to the workers in almost equal quantities.